Reprising Roles: The Lived Experiences of GED Program Repeaters - Patricia Leong Kappel (Adult Education Research Conference, 2013)
Understanding the repeater phenomenon of students enrolled in GED preparatory programs, the factors that prompt their exits and initiate their returns, and the experiences they bring to and take from each new engagement can inform the programmatic and persistence strategies of adult basic education practitioners.